Effect of tetracycline on experimental Venezuelan Equine encephalitis Intection. Preliminary comunication - Negrette, Américo; Soto Escalona, Armando; Ryder, Slavia (Investigación Clínica, 2013)
Mice were inoculated with 10 LD50 of Venezuelan equine encephalitis virus and 1.5 mgs, daily of tetracycline. At the end of the experiment almost half of the group which had received virus and antibiotic were alive while those with virus only had all died.